Lamellibrachia barhami, gen. nov. sp. nov. (Pogonophora), from the Northeast Pacific - Webb, Michael (Bulletin of Marine Science, 1969)
Lamellibrachia barhami, gen. nov., sp. nov., is a large and unique pogonophore which has been assigned to the Afrenulata, class nov.; order Vestimentifera, order nov.; and family Lamellibrachiidae, fam. nov. All previously known Pogonophora are included in a new class, the Frenulata, class nov. The fundamental distinction between the two classes lies in the presence or absence of a bridle (frenulum). The tentacular crown is formed of numerous, fused, horseshoe-shaped tentacle lamellae arranged concentrically around a central paired lophophoral organ. The second segment is characterized by two body folds meeting mid ventrally and enclosing a vestimental tube in which lie two ciliated grooves, at the posterior ends of which open the male and female genital ducts. The trunk, comprising 89 per cent of the total body length, is undifferentiated. The terminal body region, the true metasoma, is without setae. There is a pair of simple ciliated excretory ducts opening by a common excretory pore into a ventral groove at the base of the tentacular crown. The heart is a simple muscular elaboration of the anterior end of the ventral blood vessel. The second, or vestimental region, is without coelomic cavities for most of its length; however, the paired coelomic cavities of the trunk project into the posterior end of the vestimental region. The brain is large, and from it arises a pair of intra-epidermal nerve cords which extend the full length of the vestimental region; thereafter they join and form the median intra-epidermal nerve cord of the trunk. Associated with the brain and the nerve cords are the characteristic dorsal tubes.
World Polychaeta Database (WPolyDb)